Extended validation of a graph-based modelling methodology for high-pressure networks. Issue 15 (2019) - Niederberger, S.; Orjuela, R.; Schleuniger, P.; Anderegg, R.; Basset, M.
Abstract: Various applications use high-pressure pumps for waterjet machining. A cutting head generates the waterjet, which is capable to cut hard and brittle materials. These cutting heads induce pressure fluctuations with respect to an a priori unknown switching pattern. This paper applies a graph-based modelling methodology on complex high-pressure networks representing different waterjet facilities. For that, network sections are assigned to homogeneous segments, each representing a local pressure state. Segments are subsequently interconnected along their fluid flow paths, resulting in a lumped parameter model. In this way, the graph-based methodology offers a flexible modelling to cope with various network topologies. The resulting mathematical models of different waterjet facilities have been verified for specific cutting head switching patterns. Measurements on a test bench show that a desired accuracy is obtained over a wide operating range from 0 to 2.45 l/min, even for a fast switching period of 0.5 seconds.